A new species of Ribes (Grossulariaceae) from Michoacán, Mexico - Durán-Espinosa, Carlos M.; Avendaño Reyes, Sergio (Instituto de Ecología, A.C., 2002)
Ribes grandisepalum, a shrub that lives in the forest of Abies in the state of Michoacan, Mexico, is proposed as a new species to science. The new taxon belongs to subgenus Coreosma section Calobotrya (Spach) Jancz. (Grossulariaceae) and is related to Ribes pringlei Rose. It is distinguished by its glandular-pubescent sepals that reach sizes of 5.5-8.5 mm in length, pedicels 7-17 mm in length and the ovary and fruit with glandular hairs.